The female athlete triade - Lucariello, A.; Iovino, S. (Sport Science - International Scientific Journal of Kinesiology, 2019)
The female athlete triad is a syndrome consisting of disordered eating, amenorrhea, and osteoporosis that was defined in 1992. In 2007, the definition was modified to a spectrum disorder involving low energy availability (with or without disordered eating), menstrual dysfunction, and low bone mineral density. Low energy availability, from either dietary restriction or increased expenditure, is the factor that leads to the pathological states of menstrual function and bone mineral density. Athletes especially at risk are those in sports requiring leanness or low body weight. Prevention and early recognition using a team approach in patients with any component of the triad disorders is essential to ensure timely intervention and to prevent long-term adverse health effects.